Investigation of the Nature of CgCDPK and CgbHLH001 Interaction and the Function of bHLH Transcription Factor in Stress Tolerance in Chenopodium glaucum - Zhou, Zixin; Wang, Juan; Zhang, Shiyue; Yu, Qinghui; Lan, Haiyan (Frontiers in Plant Science, 2021)
Calcium dependent protein kinase (CDPK) and its substrates play important roles in plant response to stress. So far, the documentation on the characterization of the CDPK and downstream interaction components (especially transcription factors, TFs) is limited. In the present study, an interaction between CgCDPK (protein kinase) and CgbHLH001 (TF) (accession No. MT797813) from a halophyte Chenopodium glaucum was further dissected. Firstly, we revealed that the probable nature between CgCDPK and CgbHLH001 interaction was the phosphorylation, and the N-terminus of CgbHLH001, especially the 96th Serine (the potential phosphorylation site) within it, was essential for the interaction; whereas the mutation of 96Ser to Alanine did not change its nuclear localization, which was determined by the N-terminus and bHLH domain together. Furthermore, we verified the function of CgbHLH001 gene in response to stress by ectopic overexpression in tobacco, the transgenic lines presented enhanced stress tolerance probably by improving physiological performance and stress-related gene expression. In conclusion, we characterized the biological significance of the interaction between CDPK and bHLH in C. glaucum, and verified the positive function of CgbHLH001 in stress tolerance, which may supply more evidence in better understanding of the CDPK signaling pathway in response to adversity.